The Poetic Language of John Keats in Mirror of Translation: “Ode on a Gracian Urn” in Focus - Mehrpooya, Abbas (LANGUAGE ART, 2023)
The present essay includes a Persian rendition of an ode by John Keats under the name of “Ode on a Gracian Urn” and by reviewing vis-à-vis the Persian translation and the original poem, it attempts to open a narrow window to the lingual features in the poetic art of this English poet. In this interlingual transaction, that is conducted by employing the strategy of “forignization” or retaining the “forignness” of the source text, “defamiliarization” of the translated text is an extralingual aftereffect which has taken shape during this translational transaction. In this pursuit, by selecting the “Ode on a Gracian Urn” that is itself an acclaimed poem in the sphere of English literature and also among John Keats’ celecrated odes, effort has been made to reveal a brighter visage of the what and how of the stylistic and aesthetic dexterity in the poetic language of this English poet and its reflection in Persian transversification.